Partitioning of arsenic in low and high arsenic accumulating rice (Oryza sativa) cultivars - Roy, Arkaprava; Datta, Siba Prasad; Barman, Mandira; Bhattacharyya, Somnath; Meena, Mahesh Chand; Golui, Debasis; Trivedi, Vivek Kumar (The Indian Journal of Agricultural Sciences, 2020)
In view of limited information, an attempt has been made to work out the distribution pattern of arsenic (As) between root and shoot of high and low grain-As accumulating rice cultivars (HAC and LAC, respectively). For this purpose, a solution culture experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi during kharif 2018-19 with two doses of As (@ 0 and 100 µg/L) and four rice cultivars comprising one HAC (IR-36) and three LACs (Khitish, Satabdi and Badshabhog). Results indicated that the biomass yields were not affected either by As or by cultivars. The highest root As content was recorded with Khitish (4.64 mg/kg), whereas, IR-36 showed the lowest value (2.00 mg/kg) but shoot As content did not vary with cultivars. Cultivars followed almost similar trends for As uptake. The highest translocation coefficient of As from root to shoot ranged from 0.52 (IR-36) to 0.31 (Khitish). It is clear from the study that LACs are more efficient in storing As in root, even though they uptake higher amount of As at the initial phase of growth, whereas, As is mobilized from root to above ground parts more efficiently in case of HACs. Thus, partitioning of As between root and shoot appears to be an important characteristic of rice (Oryza sativa L.) cultivars responsible for differential accumulation of As.